Long-Term Effect of Ultrathin-Strut Versus Thin-Strut Drug-Eluting Stents in Patients With Small Vessel Coronary Artery Disease Undergoing Percutaneous Coronary Intervention: A Subgroup Analysis of the BIOSCIENCE Randomized Trial. (August 2019) - Iglesias, Juan F.; Heg, Dik; Roffi, Marco; Tüller, David; Noble, Stéphane; Muller, Olivier; Moarof, Igal; Cook, Stéphane; Weilenmann, Daniel; Kaiser, Christoph; Cuculi, Florim; Häner, Jonas; et al.
Abstract : Background: Randomized trials evaluating the Orsiro biodegradable polymer sirolimus-eluting stent (BP-SES; 60 and 80 μm strut thickness for stent diameters ⩽3 and >3 mm, respectively) did not stratify according to vessel size and failed to specify the impact of ultrathin-strut thickness on long-term clinical outcomes compared with durable polymer everolimus-eluting stents (DP-EES). We sought to assess the long-term effect of ultrathin-strut (60 μm) BP-SES versus thin-strut (81 μm) DP-EES on long-term outcomes in patients undergoing percutaneous coronary revascularization for small vessel disease. Methods: In a subgroup analysis of the randomized, multicenter, noninferiority BIOSCIENCE trial, patients with stable coronary artery disease or acute coronary syndrome randomly assigned to treatment with BP-SES or DP-EES were stratified according to vessel size (⩽3 mm versus >3 mm) as a surrogate to compare patients treated with ultrathin-strut versus thin-strut drug-eluting stent. The primary end point was target lesion failure, a composite of cardiac death, target vessel myocardial infarction, and clinically indicated target lesion revascularization, within 5 years. Results: Among 2109 patients, 1234 (59%) were treated for small vessel disease. At 5 years, target lesion failure occurred in 124 patients (cumulative incidence, 22.3%) treated with ultrathin-strut BP-SES and 109 patients (18.3%) treated with thin-strut DP-EES (rate ratio, 1.22; 95% CI, 0.94–1.58; P =0.13). Cumulative incidences of cardiac death, target vessel myocardial infarction, and clinically indicated target lesion revascularization and definite stent thrombosis at 5 years were similar in patients treated with ultrathin-strut BP-SES and thin-strut DP-EES. After adjustment for potential confounders, there was no significant interaction between vessel size and treatment effect of BP-SES versus DP-EES. Conclusions: We found no significant difference in clinical outcomes throughout 5 years between patients with small vessel disease treated with ultrathin-strut BP-SES versus thin-strut DP-EES. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01443104. Abstract : Supplemental Digital Content is available in the text.